Три осенних дня: [роман] - Абдуллаев Чингиз Акифович (2003)
Экземпляры: ф.14 (2003) / Инвентарный номер: 47077 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44